Tax Aggresiveness Analyis: The Role of Internal Financial Factors - Mulyani, Susi Dwi; Fitria, Giawan Nur; Tarmidi, Deden (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2024)
Research Originality: This research may suggest a deeper relationship between internal company factors and tax aggressiveness, which has not been studied explicitly. Many studies examine the influence of external factors, but this study can highlight how a company's internal financial and tax management decisions can influence tax aggressiveness.Research Objectives: This study investigates the influence of several financial factors, such as thin capitalization, financial distress, and earnings management, on tax aggressiveness.Research Methods: This study analyzed 310 data from manufacturing companies listed on the Indonesian Stock Exchange from 2019 to 2023.Empirical Results: This study found that the high thin capitalization range can reduce tax aggressiveness. Conversely, earnings management is one tool used by management to reduce tax aggressiveness, while financial distress has no impact on tax aggressiveness.Implications: The study suggests that while certain financial practices influence tax aggressiveness, broader factors such as financial stability, investor relations, and risk management also play a significant role.JEL Classification: M41, H26